Odpowiedzi

Najlepsza Odpowiedź!
2009-10-19T22:39:30+02:00
2009-10-19T22:48:46+02:00
A)x-3x+1>-5+8x
x-3x-8x>-5-1
-10x>-6/:-10
x<6/10
x<3/5
e)2+x/3-3-x/6>-1 /*6
2(2+x)-3+x>-1
4+2x-3>-1
2x>-1-4+3
2x>2/:2
x>1
f) pomnoz przez 6 ,czyli
3(x2-16)-2>x+4+3(x2-4x+4)
3x2-48-2>x+4+3x2-12x+12
3x2-3x2-x+12x>4+12+48+2
11x>66/:11
x>6
g) pomnóż przez 3 czyli
x2-8x+16+x=<1-3x+x2
4x=<-15/:4
x=<-15/4
x=<3 i 3/4
h)pomnoz przez 10
4x2-1+11=>2(x2+2x+1)+2x2
4x2-1+11=>2x2+4x+2+2x2
-4x=>2+1-11
-4x=>12/:-4
x=<-3
i) pomnoz przez 4
2x2+3x+3=>2(1+2x+x2)
2x2+3x+3=>2+4x+2x2
-x=>-1/:-1
x=<1
j)pomnoz przez 2
4x2-25<-1-x2-6x-9+5x2
6x<-1-9+25
6x<-15/:6
x<-2 i 3/6


1 5 1
2009-10-19T23:39:47+02:00
J)
4x2-25<-1-x2-6x-9+5x2
6x<-1-9+25
6x<-15/:6
x<-2 i 3/6
f)
3(x2-16)-2>x+4+3(x2-4x+4)
3x2-48-2>x+4+3x2-12x+12
3x2-3x2-x+12x>4+12+48+2
11x>66/:11
x>6
g)
x2-8x+16+x=<1-3x+x2
4x=<-15/:4
x=<-15/4
x=<3 i 3/4
h)
4x2-1+11=>2(x2+2x+1)+2x2
4x2-1+11=>2x2+4x+2+2x2
-4x=>2+1-11
-4x=>12/:-4
x=<-3
i)
2x2+3x+3=>2(1+2x+x2)
2x2+3x+3=>2+4x+2x2
-x=>-1/:-1
x=<1
e)
2+x/3-3-x/6>-1 /*6
2(2+x)-3+x>-1
4+2x-3>-1
2x>-1-4+3
2x>2/:2
x>1
a)
x-3x+1>-5+8x
x-3x-8x>-5-1
-10x>-6/:-10
x<6/10
x<3/5